SANITARY ASSESTMENT IMPROVEMENT OF THE CATTLE HALFBEEF AFFECTED BY SARKOTSYSTS - Букалова, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
This research is implemented in order to determine a necessity of additions to the «Rules of antemortal meat veterinary inspection and meat products» was approved by the State Department of Ukraine Veterinary Medicine decree on 07.06.2002, reg. № 28 and registered with the Ministry of Justice of Ukraine on 21.06.2002, reg. № 524/6812. It was established that the livestock products were received from the animals effected by sacrocysts depending on the invasion intensity had the worst organoleptic and physicochemical characteristics of meat, a low nutritional and biological value. These products are the potential source of a food poisoning for people due to the presence of conditionally pathogenic and pathogenic microflora. It was proved a bacteriological necessity research of the half-carcasses affected by sarcocysts for a detection of the toxigenic microorganisms. It was based on the research data the veterinary and sanitary assessment ways of improvement of the slaughtered animals’ carcasses for sarkocystosis were proposed